Quantifying the mortality caused by the H1N1 influenza virus during the 2009 pandemic in Mexico - Eusebio Perez-Flores; Juan Carlos Izquierdo-Puente; Jose Juan Castillo-Perez; Gustavo Ramírez-Rosales; Israel Grijalva-Otero; Constantino Lopez-Macias; Roman Alejandro Garcia-Ramirez; Concepción Grajales-Muñiz; Juan Manuel Mejia-Arangure (Journal of Infection in Developing Countries)
Introduction: The frequency and mortality of the pandemic caused by influenza A(H1N1)pdm09 might have been underestimated, especially in developing countries. This study was designed to quantify the possible underestimation of pandemic influenza mortality and evaluate the concordance between the data reported for A(H1N1)pdm09 mortality and the causes of death reported during the pandemic period of April 2009 to February 2010. Methodology: The death certificates of 754 confirmed cases of A(H1N1)pdm09 infection were included in the study. Data was analyzed using the United States Centers for Disease Control and Prevention’s statistical model accounts for the variability in the proportion at each step using the Monte Carlo probabilistic model sampled from a uniform probability distribution. Results: A total of 1,969 deaths were estimated, with an estimated lethality of 5.53 per 100,000 (range, 3.5-8.76 per 100,000) in contrast with the 754 deaths and a lethality of 1.98 per 100,000 infected patients officially reported. In 631 of 754 (83.7%) death certificates from A(H1N1)pdm09 influenza-positive patients, influenza was not mentioned as a cause of death. Conclusions: It is possible that the mortality of the pandemic was three times higher than officially reported in Mexico. One source of error that could explain this underestimation is in the completion of death certificates, because in > 80% of confirmed cases of infection with influenza virus, it was not reported as the cause of death.